Investment analysis of soybean production system in sugarcane renewal areas - Santos, David Ferreira Lopes [UNESP]; Farinelli, Juliana Borba de Moraes [UNESP]; Horita, Kandy [UNESP]; da Silva, Bruna Luísa [UNESP]; Souza, Camila Aparecida Fonseca [UNESP] (My University, 2020)
Soybeans are an important crop for Brazil's economy, and in the 2016/2017 harvest, it produced 113,9 million tons, representing 32,43% of world production. Despite its representativeness to soybeans while an oilseed has been little explored in sugarcane renovation areas, whose total hectares can reach 1 million / year in Brazil. Given this opportunity, this study economically evaluates two systems of planting, in three different rural property profiles, with three different price scenarios and with use of leased area and own in the State of São Paulo. It was verified in 36 possibilities that the production of soybeans in a sugarcane renewal area is feasible for all planting systems, in a leased area and in the three ownership profiles. Only in the pessimistic price scenario, the crop proved to be unfeasible for leased area and conventional planting in its own area. It was verified that no-tillage besides conservationist is the one that presents the best economic performance and the use of leased area can leverage the economic results. The combination of the Discounted Cash Flow approach with the Cost-Volume-Profit Analysis allowed a differentiated analysis of the investment by pointing out the minimum limits that varied between 29 ha and 1,065 ha to economically make production feasible between the different strategies and production profile and scenario price.
Keywords: Agribusiness; Breakeven point; Cost-Volume-Profit-Analysis; Economic Viability; Return on Investment